Effect of Enterococcus avium and Enterococcus casseliflavus supernatant and pellet on Klebsiella pneumoniae biofilm formation - Keywan jebrail Chicho; Sawsan Mohammed Sorchee (Tikrit Journal of Pure Science, 2023)
Enterococcus is cocci shaped, gram positive, oxidase and catalase negative, facultatively anaerobic, and does not produce spores. It  is one of the principal genera that belong to the group of ‘lactic acid bacteria’ (LAB), which also includes Streptococcus and Lactobacillus. The study aimed to detect Enterococcus spp. bacteria using molecular diagnostics .Twenty-one isolates (21%) from 100 samples belonging to Enterococcus spp. were obtained. Three isolates belonging to (two) Enterococcus avium (9.52%) one of them isolated from Kaymak and the other from yoghurt, the other one was (one) Enterococcus casseliflavus (4.76%) which isolated from Ricotta (Made by buffalo milk).  After diagnosing by Vitek-2 system of Klebsiella pneumoniae bacteria and detecting its biofilm formation by ‘Congo Red Agar’ method with antibiotic test, the effect of the Enterococcus avium and Enterococcus casseliflavus (supernatants and pellets) on its biofilm formation was tested. Moreover, when compare; to the control group, the effect was highly ‘significant’ (p.0.0069).